ANALISIS PENERAPAN BAURAN PEMASARAN SYARIAH DALAM PEMASARAN PRODUK PEMBIAYAAN BERBASIS BAGI HASIL PADA PT. BANK NAGARI - Alwil Haddad Annur; Rizal; Himyar Pasrizal (STKIP Subang, 2025)
The subject matter of this thesis is the marketing of financing products at PT Bank Nagari which continues to decline. The purpose of this research is to find financing products, procedures and marketing mix used in marketing profit-sharing-based financing products at PT Bank Nagari. The type of research used in this research is field research with a qualitative approach. The data collection techniques used are initial surveys, in-depth interviews and documentation. The data analysis technique in this research is the Miles and Huberman method. The results of this study indicate that the financing products available at PT Bank Nagari consist of mudharabah, musyarakah, murabahah, ijarah and others. However, the most attractive to customers is murabahah financing. The marketing procedure for profit-sharing-based financing products at PT Bank Nagari is in accordance with the SOP and is supervised by DPS, besides that the marketing of profit-sharing-based financing products at PT Bank Nagari has also kept up with the times. The implementation of the sharia marketing mix at PT Bank Nagari has been carried out based on the 7Ps, namely product, price, place, promotion, people, physical evidence and process. However, the marketing mix that tends to be carried out is promotion.